Besonderheiten der Realisierung von prosodischen Parametern in der Predigt: Ergebnisse der experimentell-phonetischen Untersuchung - Скрипняк, Т.Л. (Культура народов Причерноморья, 2007)
Prosody effects perception and evaluation of a sermon by a recipient who attaches his own connotative meaning to the oral text. Results of auditive and acoustic analysis show differences in prosodic realization of sermon fragments. Method of semantic differential allows to fix changes in reactions and perception of recipients during listening of a sermon.